KIR/HLA ligands immunogenetics markers associated with outcome of hepatitis B virus infection in the Bulgarian population - Varbanova, Viktoria; Popov, Georgi; Grigorova, Veneta; Petrova, Diana; Naumova, Elissaveta; Mihaylova, Anastasiya (Biomedical papers, 2021)
Background. Hepatitis B virus (HBV) infection is one of the most common infections worldwide, having negative impact on world health due to the tendency for chronification with late complications such as liver cirrhosis and hepatocellular carcinoma. Natural killer (NK) cells as part of innate antiviral defense influence the clinical course of HBV infection: elimination of the virus or chronic disease. Aim. Therefore, we investigated the polymorphisms of the main gene systems, regulating NK-cell function: killer cell immunoglobulin-like receptors (KIRs) and their appropriate HLA class I ligands in 144 HBV infected patients (124 chronic carriers and 20 spontaneously recoved) and 126 ethnically matched healthy controls from the Bulgarian population in a case-control study. Methods. KIRs and HLA ligands were determined by PCR-SSP or PCR high-resolution typing methods. Results. KIR2DL5B allele variant was significantly less frequent in spontaneously recovered (SR) patients compared to healthy controls (10.0% vs. 45.5%, Pcorr=0.006). The presence of KIR3DL1*004 allele was higher in chronic HBV carriers (CH) than in controls (33.1% vs. 17.6%, Pcorr=0.036). Additionally, SR patients differed from healthy individuals by the lower frequency of HLA-Bw4Ile80 group ligands (30.0% vs 63.7%, P=0.015). Three KIR genotypes were found more frequent in healthy in comparison with HBV infected individuals: ID2 (13.5% vs 5.6%, P=0.025), KIR genotype containing 6 activating KIRs (18.0% vs 7.6%, P=0.017), and KIR genotype composed of 4 activating and 5 inhibitory KIRs (23.8% vs 5.6%, P=0.001). Conclusion. These data suggest that inherited KIR and HLA class I ligand polymorphisms may influence the clinical course of HBV infection.
Keywords: killer immunoglobuline-like receptors; KIR HLA ligands; hepatitis B infection